Advances in algal biomass pretreatment and its valorisation into biochemical and bioenergy by the microbial processes. (August 2022) - Kant Bhatia, Shashi; Ahuja, Vishal; Chandel, Neha; Gurav, Ranjit; Kant Bhatia, Ravi; Govarthanan, Muthusamy; Kumar Tyagi, Vinay; Kumar, Vinod; Pugazendhi, Arivalagan; Rajesh Banu, J.; Yang, Yung-Hun
Graphical abstract: Highlights: Algae can capture carbon dioxide and produce many valuable compounds. Residual algal biomass is rich in various polysaccharides. Biomass requires various pretreatments to release free sugars. Algal hydrolysate can be used as feedstock for microbial fermentation. Hydrolysate can be valorised into bioenergy and biochemicals. Abstract: Urbanization and pollution are the major issues of the current time own to the exhaustive consumption of fossil fuels which have a detrimental effect on the nation's economies and air quality due to greenhouse gas (GHG) emissions and shortage of energy reserves. Algae, an autotrophic organism provides a green substitute for energy as well as commercial products. Algal extracts become an efficient source for bioactive compounds having anti-microbial, anti-oxidative, anti-inflammatory, and anti-cancerous potential. Besides the conventional approach, residual biomass from any algal-based process might act as a renewable substrate for fermentation. Likewise, lignocellulosic biomass, algal biomass can also be processed for sugar recovery by different pre-treatment strategies like acid and alkali hydrolysis, microwave, ionic liquid, and ammonia fiber explosion, etc. Residual algal biomass hydrolysate can be used as a feedstock to produce bioenergy (biohydrogen, biogas, methane) and biochemicals (organic acids, polyhydroxyalkanoates) via microbial fermentation.